Upland rice intercropped with green manures and its impact on the succession with common bean - Meirelles, F. C. [UNESP]; Cavalcante, A. G. [UNESP]; Gonzaga, A. R. [UNESP]; Filla, V. A. [UNESP]; Roms, R. Z. [UNESP]; Coelho, A. P. [UNESP]; Arf, O. [UNESP]; Lemos, L. B. [UNESP] (Cambridge University Press (CUP), 2021)
The aim of this work was to verify the possibility of intercropping rice with green manures, as well as the impact of the dry biomass yield of these intercropping systems on common bean in succession, evaluating the agronomic and qualitative performance of grains from both crops. The experiment was conducted in Southeastern Brazil in the years 2018 and 2019, with succession of rice (spring/summer) and common bean (autumn/winter). The treatments were composed of cropping systems with rice as a sole crop and intercropped with forage peanut, calopo, Crotalaria breviflora, Crotalaria spectabilis, stylo, jack bean and dwarf pigeon pea. No intercropping increased the system's yield compared to sole-crop rice, but intercropping of rice with forage peanut and stylo promoted grain yield and quality similar to those of sole-crop rice. Intercropping with C. breviflora affected the agronomic and qualitative performance of rice. Common bean yield after rice intercropped with dwarf pigeon pea, C. spectabilis and C. breviflora was similar in yield after sole-crop rice, while the other intercrops reduced common bean yield. Common bean grain quality was not affected by the cultivation of rice as sole crop and intercropped with green manures. Although none of the intercropping systems increased yield compared to sole-crop rice (control), it can be concluded that the intercropping of upland rice is viable depending on the green manure species, allowing greater biomass production per area that can help long-term soil conservation and increase the system's yield.
Keywords: Autumn-winter beans; cover crops; Oryza sativa L; Phaseolus vulgaris L; polyculture